Sagot :
Step-by-step explanation:
a. x = -3
[tex]f( - 3) = { (- 3)}^{2} + 3( - 3) - 2[/tex]
[tex]f( - 3) = 9 - 9 - 2[/tex]
[tex]f( - 3 ) = - 2[/tex]
b. x = 0
[tex]f(0) = {(0)}^{2} + 3(0) - 2[/tex]
[tex]f(0) = - 2[/tex]
c. x = 2
[tex] f(2) = {(2)}^{2} + 3(2) - 2[/tex]
[tex]f(2) = 4 + 6 - 2[/tex]
[tex]f(2) = 10 - 2[/tex]
[tex]f(2) = 8[/tex]
d. x = 3
[tex]f(3) = {(3)}^{2} + 3(3) - 2[/tex]
[tex]f(3) = 9 + 9 - 2[/tex]
[tex]f(3) = 9 - 2[/tex]
[tex]f(3 ) = 7[/tex]
e. x = - 2/3
[tex]f( - \frac{2}{3}) = {( - \frac{2}{3}) }^{2} + 3( - \frac{2}{3}) - 2 [/tex]
[tex]f( - \frac{2}{3}) = \frac{4}{9} - 2 - 2[/tex]
[tex]f( - \frac{2}{3} ) = \frac{4}{9} - 4[/tex]
[tex]f( - \frac{2}{3}) = \frac{4}{9} - \frac{4}{1} = \frac{4 - 36}{9} = - \frac{32}{9} [/tex]
[tex]f( - \frac{2}{3 } ) = - \frac{32}{9} [/tex]
f. x = 0.005
[tex]f(0.005) = {(0.005)}^{2} + 3(0.005) - 2[/tex]
[tex]f(0.005) = 0.000025 + 0.015 - 2[/tex]
f(0.005) = -1.984975